Adiponectin, Leptin, and IGF-1 Are Useful Diagnostic and Stratification Biomarkers of NAFLD - Marques, Vanda; Afonso, Marta B.; Bierig, Nina; Duarte-Ramos, Filipa; Santos-Laso, Álvaro; Jimenez-Agüero, Raul; Eizaguirre, Emma; Bujanda, Luis; Pareja, Maria J.; Luís, Rita; Costa, Adília; Machado, Mariana V.; et al. (Frontiers in Medicine, 2021)
Objective: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease where liver biopsy remains gold-standard for diagnosis. Here, we evaluated circulating metabolism-related hormones as non-invasive NAFLD biomarkers, and their correlation with the metabolome. Materials and Methods: Leptin, adiponectin and insulin-like growth factor 1 (IGF-1) serum levels were measured by ELISA in two independent cohorts of biopsy-proven obese NAFLD patients and healthy liver controls (discovery: 38 NAFLD, 13 controls; validation: 194 NAFLD, 31 controls), and correlated with clinical data, histology, genetic parameters and serum metabolomics. Results: In both cohorts, leptin increased in NAFLD vs. controls (discovery: AUROC 0.88; validation: AUROC 0.83; p < 0.0001). Leptin levels were similar between obese and non-obese healthy controls, suggesting that obesity is not a confounding factor. In discovery cohort, adiponectin was lower in nonalcoholic steatohepatitis (NASH) vs. nonalcoholic fatty liver (AUROC 0.87; p < 0.0001). For validation cohort significance was attained for homozygous for PNPLA3 allele c.444C (AUROC 0.63; p < 0.05). Combining adiponectin with specific serum lipids improved assay performance (AUROC 0.80; p < 0.0001). For validation cohort, IGF-1 was lower with advanced fibrosis (AUROC 0.67, p < 0.05), but combination with international normalized ratio (INR) and ferritin increased assay performance (AUROC 0.81; p < 0.01). Conclusion: Serum leptin discriminates NAFLD and adiponectin combined with specific lipids stratifies NASH. IGF-1, INR and ferritin distinguish advanced fibrosis.